The Digitalization of Indonesia’s Commercial Court System for Bankruptcy And Debt Restructuring Proceedings: Digitalisasi Sistem Peradilan Niaga Indonesia untuk Proses Kepailitan dan Restrukturisasi Utang - Lie, Sarah Milenia; Sudiro, Ahmad (Perspektif Hukum, 2025)
he COVID-19 pandemic triggered a global economic downturn that significantly impacted Indonesia, resulting in widespread financial distress and an increase in corporate insolvencies. Amid these challenges, Indonesia’s judiciary accelerated the adoption of digital judicial mechanisms through the implementation of the electronic court (e-Court) system. Rooted in a series Supreme Court Regulation, including the most recent Supreme Court Regulation No. 7 of 2022, the e-Court framework modernized court administration and enabled remote hearings, ensuring that justice remained accessible despite social restrictions. This study employs a normative legal research method, specifically statutory and case-based approach, to analyze the evolution and application of the e-Court system, particularly in the context of Suspension of Debt Payment Obligations (Penundaan Kewajiban Pembayaran Utang or PKPU) proceedings as governed by Law No. 37 of 2004. Using the Garuda Indonesia case (Decision No. 425/Pdt.Sus-PKPU/2021/PN.Niaga.Jkt.Pst.) as a reference, the research highlights how e-Court supported judicial continuity and upheld the principles of simplicity, promptness, and affordability as mandated under Article 2(4) of Law No. 48 of 2009 on Judicial Power. The findings underscore e-Court’s crucial role in maintaining economic and judicial resilience, while also identifying challenges regarding procedural legitimacy, technological literacy, and equitable access.